Analysis of Social Entrepreneurship Business Model Glenys Store - Nurmelinda, Risma Dewi; Yusuf, Ismail (A Social Science and Entrepreneurship Journal, 2021)
The purpose of Analysis of Social Entrepreneurship Model Glenys Store. This study aims to: (a) Knowing the meaning of social models, (b) Knowing social enterprise models, (c) Knowing the Glenys Store social business model. This research was conducted by utilizing a literature study. This research approach is qualitative. The result of this research is the business model method that can be used is the Business Model Canvas which is a logical description model of how an organization creates, delivers and captures value. Therefore, the suitable model for Glenys Store based on BMC is the Service Subsidization Model.